Effect of Grazing Exclusion and Rotational Grazing on Soil Aggregate Stability in Typical Grasslands in Inner Mongolia, China - Dong, Lei; Zheng, Ying; Martinsen, Vegard; Liang, Cunzhu; Mulder, Jan (Frontiers in Environmental Science, 2022)
Soil aggregate is extremely important for soil health and sustainable land management. Overgrazing has caused serious degeneration of grassland in the past decades and how to restore the degraded soil through grazing management is urgently needed. In this research, we investigated effects of long-term grazing exclusion and short-term rotational grazing with different grazing intensities on aggregate stability in the upper 10 cm of soil at two grazing sites in Xilinhot, Inner Mongolia. Treatments included long-term (34 years) exclusion, moderate-term (21 years) exclusion, and continuous grazing at adjacent reference plots. In addition, effects of rotational grazing under different grazing intensity [i.e., no grazing (0 day/month), light grazing (3 days/month), moderate grazing (6 days/month) and high grazing (12 days/month)] were investigated after five years. Stability of aggregate fractions were determined using wet sieving. Our results showed that the stable aggregates fraction were significantly increased under grazing exclusion for both fine (0.25 - 1 mm) and coarse (1 - 2 mm) size fractions. At the rotational grazing site, stability of fine aggregates was significantly enhanced under grazing compared with no grazing, while there was little influence on stability of coarse aggregates. Our results showed that grazing exclusion significantly increased soil aggregate stability and the peak appeared in moderate-term exclusion, meanwhile, rotational grazing had little influence on aggregate stability. We suggest that rotational grazing rather than long-term grazing exclusion is a better way for soil aggregate stability and soil health, and current grazing prohibition policies may need to be adjusted.